Exposure to heavy metals and trace minerals in first trimester and maternal blood pressure change over gestation. (August 2021) - Liu, Tiange; Zhang, Mingyu; Rahman, Mohammad L.; Wang, Xiaobin; Hinkle, Stefanie N.; Zhang, Cuilin; Mueller, Noel T.
Highlights: We examined heavy metals and trace minerals mixture and blood pressure in pregnancy. Overall, the mixture was positively associated with blood pressure in early pregnancy. Cu and Se was each individually linked with blood pressure and its weekly change. The mixture was not associated with hypertensive disorders during pregnancy. Abstract: Background: While several heavy metals and trace minerals have been linked with hypertensive disorders during pregnancy (HDP) in women, no studies have estimated the relationship of exposure to these chemicals, both independently and as a mixture, with systolic blood pressure (SBP) or diastolic blood pressure (DBP) over gestation. Objectives: We examined individual and joint effects of 1 st trimester chemicals with SBP and DBP over gestation, and whether those chemicals were associated with HDP. Methods: We used data from 1832 non-obese pregnant women with low-risk antenatal profiles from the Eunice Kennedy Shriver National Institute of Child Health and Human Development Fetal Growth Studies - Singleton cohort (2009–2013). In plasma collected from women at 8–13 weeks' gestation (baseline enrollment), we measured heavy metals, barium (Ba), cesium (Cs), antimony (Sb), as well as trace minerals, cobalt (Co), copper (Cu), molybdenum (Mo), selenium (Se), and zinc (Zn). We obtained BP at baseline and throughout gestation until delivery and diagnosis of HDP from medical records. We used Bayesian Kernel Machine Regression (BKMR) as well as traditional linear and logistic regressions to examine the cross-sectional associations of chemicals with baseline BP and HDP. We used linear mixed effect regression to examine longitudinal associations between chemicals and rate of weekly change in BP in each trimester. We adjusted for sociodemographic and lifestyle factors and pre-pregnancy body mass index in all models. Results: BKMR revealed that comparing the entire chemical mixture at the 90 th percentile vs. the 50 th percentile was associated with a 1.61 mmHg (95% CI: 0.41, 2.81) higher SBP and a 1.09 mmHg (0.10, 2.09) higher DBP. No interactions were observed between chemicals. Accounting for chemical co-exposure in BKMR, each interquartile range (IQR) increment in Cu was associated with a 0.67 mmHg (0.02, 1.32) higher SBP and a 0.60 mmHg (0.08, 1.12) higher DBP at baseline; each IQR increment in Se was associated with a 0.67 mmHg (0.05, 1.29) higher SBP but not DBP. In longitudinal analyses, women with higher (i.e., above median concentration) baseline Cu had a 0.09 mmHg (0.01, 0.17) and 0.06 mmHg (0.001, 0.12) larger weekly decrease in SBP and DBP in 2 nd trimester, respectively. Women with higher baseline Ba had a 0.12 mmHg (0.04, 0.20) larger weekly increase in SBP in 2 nd trimester, while women with higher Cs had a 0.05 mmHg (0.01, 0.10) larger weekly increase in DBP in 3 rd trimester. None of the chemicals examined were significantly associated with HDP. Conclusions: In this multi-ethnic cohort of women with low antenatal risk, plasma metals and trace minerals in early pregnancy, both individually and as a mixture, were statistically significantly associated with BP during gestation in small magnitude and in different directions, but not with HDP. The implications of these findings for women's postpartum BP and future cardiovascular health remains to be investigated.